How to Improve Student Understanding in Learning Science by Regulating Strategy in Language Education? Definition, Factors for Enhancing Students Comprehension, and Computational Bibliometric Review Analysis - Suherman, Irman; Fauziah, Siti Pupu; Roestamy, Martin; Bilad, Muhammad Roil; Abduh, Amirullah; Nandiyanto, Asep Bayu Dani (Universitas Negeri Makassar, 2023)
The purpose of this study is to explain language education development research for improving student comprehension in learning science. This study also reviews the definition of these strategies, identifies factors that contribute to improving students' comprehension, and conducts a computational bibliometric review analysis to determine the efficacy of these approaches using Google Scholar with keywords